Something I’ve been going over with baker/Jan (and briefly VA) on Discord:
So (x+n)(x+n) = 2d(n-1) + nn + f – 1. We’ve known this for months now. You can create the smaller square that you’d add to c to make the bigger square with 2d(n-1), nn, f and -1. I was just thinking about why VQC brought up sqrt(2d) and sqrt(e). 2d(n-1)+nn+f-1 is always going to be a square with a valid cell. So if we take the square root of 2d(n-1)+nn+f-1, we’ll get x+n, right?
x+n = sqrt(2d(n-1)+nn+f-1)
This is true, and can be verified with test cases. e.g. c559, (30:5:6) = {30:5:23:10:13:43} f=17
x+n = sqrt(2d(n-1)+nn+f-1)
10+5 = sqrt(46(4)+25+17-1)
15=sqrt(225) (this is true)
What’s weird is when you use algebra to try to isolate sqrt(2d) or any of the other elements.
x = sqrt(2d(n-1)) + sqrt(f) - 1
This can also be represented as
x = sqrt(2d(n-1)) + sqrt(2d) – sqrt(e)
which isolates sqrt(2d) and sqrt(e), two newer elements that VQC brought up probably about a month ago now. This seems like it makes algebraic sense, right? I mean, as an example, 16=28, and sqrt(16)=sqrt(2)sqrt(8). So if you plugged in the numbers, surely you’d calculate the correct x, right? Well, this x should be 10. Let’s plug in some numbers. First with the sqrt(f) equation:
x = sqrt(2d(n-1)) + sqrt(f) – 1
x = sqrt(46(4)) + sqrt(17) – 1
x = 16.687765592
Clearly that isn’t correct. Let’s also do it with the 2d and e equation.
x = sqrt(2d(n-1)) + sqrt(2d) – sqrt(e)
x = sqrt(46(4)) + sqrt(46) – sqrt(30)
x = 14.869764374
This not only also isn’t equal to 10 but it also isn’t equal to the sqrt(f) version of the equation.
So does anyone know why this would happen? Is it us making a mistake with the algebra, or is there something weird going on with these squares?